Non-Parametric Modeling of Partially Ranked Data - Lebanon, Guy; Mao, Yi (Journal of Machine Learning Research, 2008)
Statistical models on full and partial rankings of n items are often of limited practical use for large n due to computational consideration. We explore the use of non-parametric models for partially ranked data and derive computationally efﬁcient procedures for their use for large n. The derivations are largely possible through combinatorial and algebraic manipulations based on the lattice of partial rankings. A bias-variance analysis and an experimental study demonstrate the applicability of the proposed method.